Increased Plasma Levels of Danger-Associated Molecular Patterns Are Associated With Immune Suppression and Postoperative Infections in Patients Undergoing Cytoreductive Surgery and Hyperthermic Intraperitoneal Chemotherapy - Leijte, Guus P.; Custers, Hettie; Gerretsen, Jelle; Heijne, Amon; Roth, Johannes; Vogl, Thomas; Scheffer, Gert J.; Pickkers, Peter; Kox, Matthijs (Frontiers in Immunology, 2018)
Introduction Danger-associated molecular patterns (DAMPs) can elicit immune responses and may subsequently induce an immune-suppressed state. Previous work showed that increased plasma levels of DAMPs are associated with immune suppression and increased susceptibility towards infections in trauma patients. Like trauma, major surgical procedures such as cytoreductive surgery (CRS) combined with hyperthermic intraperitoneal chemotherapy (HIPEC), are also thought to cause profound DAMP release. Furthermore, the incidence of postoperative infections in these patients, ranging from 10-36%, is very high compared to that observed in patients undergoing other major surgical procedures. We hypothesized that the double-hit of surgical trauma (CRS) in combination with HIPEC causes excessive DAMP release, which in turn contributes to the development of immune suppression. To investigate this, we assessed DAMP release in patients undergoing CRS-HIPEC, and investigated its relationship with immune suppression and postoperative infections. Methods In 20 patients undergoing CRS-HIPEC, blood was obtained at five time points: just before surgery (baseline), after CRS, after HIPEC, at ICU admission, and one day after surgery. Circulating levels of DAMPs (Heat Shock Protein (HSP)70, High Mobility Group Box (HMGB)1, S100A12, S100A8/S100A9, nuclear (n)DNA, mitochondrial (mt)DNA), lactate dehydrogenase (LDH, a marker of unscheduled cell death), and cytokines (TNFα, IL-6, IL-8, IL-10, MIP-1α, MIP-1β, and MCP-1) were measured. The extent of immune suppression was determined by measuring HLA-DR gene expression and ex vivo leukocytic cytokine production capacity. Results Plasma levels of DAMPs (maximum fold increases of HSP70: 2.1 [1.5-2.8], HMGB1: 5.9 [3.2-9.8], S100A8/S100A9: 3.6 [1.8-5.6], S100A12: 2.6 [1.8-4.3], nDNA 3.9 [1.0-10.8]), LDH (1.7 [1.2-2.5], and all measured cytokines increased profoundly following CRS-HIPEC. Evidence of immune suppression was already apparent during the procedure, illustrated by a decrease of HLA-DR expression compared with baseline (0.5-fold [0.3-0.9]) and diminished ex vivo pro-inflammatory cytokine production capacity. The increase in HMGB1 levels correlated with the decrease in HLA-DR expression (r=-0.46, p=0.04), and peak HMGB1 concentrations were significantly higher in the five patients who went on to develop a postoperative infection (p=0.04). Conclusion CRS-HIPEC is associated with profound DAMP release and immune suppression, and plasma HMGB1 levels are related with the occurrence of postoperative infections in these patients.